Faktor-Faktor yang Memengaruhi Remaja di Indonesia Menjadi Kecanduan terhadap Minuman Beralkohol - Ida Bagus Agung Permana Manuaba; David Hizkia Tobing (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Alcohol abuse is a growing problem around the world. Especially in adolescents, alcoholic beverages are often consumed excessively for specific purposes. Looking at the problem, the question arises what influences adolescents to become addicted to alcohol, so this paper aims to find out what factors influence adolescents in Indonesia to become addicted to alcohol. This research was conducted using a descriptive literature review method. Literature was searched and found through Google Scholar with the keywords "addiction", "alcohol", "adolescents", and "alcohol". The inclusion criteria based on these keywords were (1) presenting articles in Indonesian or English, (2) published in 2018-2023, (3) discussing factors affecting alcohol addiction, and (4) downloadable. The exclusion criteria used were (1) the article was a thesis, thesis, case study, scoping review and (2) published before 2018. The results found that adolescents who are addicted to alcohol are influenced by various factors. Namely, environmental, cultural, and personal factors. Often teenagers who are addicted to alcohol are influenced by the environment.